Analgesic grayanoids from Craibiodendron henryi. (13th August 2022) - Xiao, Shu-Meng; Liu, Yun-Bao; Qu, Jing; Ma, Shuang-Gang; Li, Yong; Yu, Shi-Shan
Abstract: Fourteen new grayanane-type diterpenes, and a known diterpene, 14 β - O -(2 S, 3 S -nilyl)-2 α, 3 β, 5 β, 6 β, 16 α -pentahydroxygrayanane, were isolated from twigs of Craibiodendron henryi W. W. Smith. The structures of the new compounds were confirmed by extensive spectroscopy. The analgesic activities of Compounds 1 –14 were evaluated by performing an acetic-acid-induced writhing test on mice. Compounds 1 –5 and 9 –14 exhibited significant analgesic activity at 5 mg/kg (intraperitoneal injection) compared to vehicle-injected mice (P < 0.001). Compounds 1, 2, 3, 4, 5, 9, 10, and 14 showed more potent activity than the other compounds. Compounds 3, 4, 10, and 14 had significant analgesic effects even at doses as low as 0.2 mg/kg, with inhibition rates of 42.2%, 36.4%, 39.6%, and 55.0%, respectively, which were equivalent to that produced by morphine at the same dose. Graphical abstract: Fourteen new grayanane-type diterpenes were isolated from twigs of Craibiodendron henryi. Compounds 3, 4, 10, and 14 had significant analgesic effects at doses as low as 0.2 mg/kg, with inhibition rates of 42.2%, 36.4%, 39.6%, and 55.0%, respectively, which were equivalent to that produced by morphine at the same dose. Image 1